2011
DOI: 10.1016/j.jconrel.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of metastasis in a 4T1 murine breast cancer model by doxorubicin carried by folate conjugated pH sensitive polymeric micelles

Abstract: This study primarily focused on the anti-metastatic activity of doxorubicin (DOX) loaded in a pHsensitive mixed polymeric micelle formed from two block polymers: poly(L-lactide) (PLLA) (Mn 3000)-b-poly(ethylene glycol) (PEG) (Mn 2000)-folate and poly(L-histidine) (PHis) (Mn 4700)-b-PEG (Mn 2000). Tumor formation and metastasis in mice were examined using a murine mammary carcinoma cell of 4T1 which is one of the most aggressive metastatic cancer cell lines. The efficacy was evaluated by tumor size, body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 25 publications
4
84
0
Order By: Relevance
“…This was consistent with the result that nanoparticles, compared to solution dosage forms, were likely to accumulate more in the liver, a major reticuloendothelial system (RES) organ, via a passive mechanism (37). Enhanced permeability and retention (EPR) due to the immature and porous vasculature of tumors (38) might have increased the uptake of nanoparticles in the liver of hepatoma rats. Considering the in vitro results (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…This was consistent with the result that nanoparticles, compared to solution dosage forms, were likely to accumulate more in the liver, a major reticuloendothelial system (RES) organ, via a passive mechanism (37). Enhanced permeability and retention (EPR) due to the immature and porous vasculature of tumors (38) might have increased the uptake of nanoparticles in the liver of hepatoma rats. Considering the in vitro results (Figs.…”
Section: Discussionsupporting
confidence: 85%
“…Early on, it has been realized that drugs in PLGA tend to have a huge initial burst release (90% release in 1 st 3 days), followed by a slow, often unpredictable core erosion release [5]- [7]. One way to overcome this challenge is through micro or nano particles [8]. The major problem is the elaborate process.…”
Section: Introductionmentioning
confidence: 99%
“…21 To reduce the acute toxicity of free doxorubicin and to improve its therapeutic efficacy, various polymeric micelle systems have been designed as delivery vehicles. [22][23][24] Studies have shown that cellular uptake of doxorubicin-loaded micelles and free doxorubicin are very different, ie, doxorubicin micelles are transported into cells by endocytosis, whereas free doxorubicin enters cells by simple diffusion. 18 In this study, we prepared composite PEG-PCL and P105 micelles using the solvent evaporation method to serve as carriers for doxorubicin.…”
Section: Discussionmentioning
confidence: 99%